PENDAMPINGAN PENGADAAN BAHAN PRAKTUKUM ZOOLOGI DAN BIOTEKNOLOGI BAGI GURU SMA DI KABUPATEN KLUNGKUNG - Wiratmini, N.I.; Sukmaningsih, A.A.S.; Narayani, I.; Pharmawati, M. (Buletin Udayana Mengabdi, 2022)
Advances in molecular biology has brought a new branch of multidiscipline study named biotechnology. To comprehend the complex nature of concepts in biology, practical and hands-on approaches are often required. This activity was a collaboration between Biology Teachers Working Group (MGMP Biologi) in Klungkung Regency with university as the facilitator, and aimed to train senior high school biology teachers in compiling learning modules as well as supplying them with the appropriate materials required in simple practical sessions, such as those in animal physiology and reproduction, as well as biotechnology. The event was held successfully, attended by total of 20 biology teachers from six senior high schools (SMA) in Klungkung District, Klungkung Regency, started by introductory lectures and followed by practical sessions on how to perform mice vaginal and sperm smear, human blood smear, and DNA extraction of plant tissues.   Keywords: practicals, zoology, biotechnology, senior high school students